Turismo cultural: contribuições para a preservação da memória do acervo raro da Bibliotheca Pública Pelotense - Cortes, Márcia Della Flora (2016)
This research is focused on cultural tourism in the scope of book collections as a way to provide an opportunity for the visiting public to know the bibliographic heritage of librarian institutions, resulting in the preservation of the memory of rare books. The study has as the root locus the Public Bibliotheca Pelotense and the objective: to explore the interest of visitors present at the "Heritage Day" to meet its rare collection, analyze the possible impacts caused by the development of tourism under the rare books collection and analyze the tourism, cultural and literary potential of this collection. The work is in a qualitative and quantitative research, in which questionnaires were used with visitors from the bibliotheca pelotense, chosen randomly, and semi-structured interviews were conducted with an active historian in the library and librarians of the National Library of Brazil responsible for coordinating the Special Collection and Rare Books Division. The research revealed that the collection of rare books of the Public Bibliotheca Pelotense awakens the interest of visitors to meet it, as well as having daily diaries of trips that address sights of the city and thus a relevant bibliographic heritage, which encourage literary tourism and at the same time become touristic products. Another result of the study indicates that cultural tourism in exposed rare collections is a way to preserve the memory and disclosure of assets, stimulating in the potential audience the sense of belonging and desire to search the library. From this, it appears that cultural tourism in the collection of rare books of the Public Bibliotheca Pelotense has potential and despite some difficulties, the institution seeks to preserve its collection and plans in the future, a new space for rare works. As a product of this dissertation, was created one lego box and a video to promote the cultural and literary tourism in the institution from its bibliographical heritage.